Computational social science : proceedings of the 2nd International Conference on New COmputational Social Science (ICNCSS 2021), October 15-17, 2021, Suzhou, Jiangsu, China /: proceedings of the 2nd International Conference on New COmputational Social Science (ICNCSS 2021), October 15-17, 2021, Suzhou, Jiangsu, China. (2022) - Unknown
No abstract available